SELEKSI BEBERAPA GENOTIPE GANDUM BERDASARKAN KOMPONEN HASIL DI DAERAH CURAH HUJAN TINGGI - Nurwanita Ekasari Putri; Irawati Chaniago; Irfan Suliansyah (Jurnal Agroteknologi, 2013)
This Research aimed to select wheat genotypes which potential to be developed in a high rainfall area. It was conducted at September 2012 to January 2013 in Alahan Panjang, Solok Regency, West Sumatera. Seventeen wheat genotypes were planted at Alahan Panjang, Solok, West Sumatera from September 2012 – January 2013, including local varieties (Nias, Selayar, Dewata). It used random design block with 3 replications and 10 samples each block. If genotypes were significant according to test f then continued by test duncan on standard 5 %. Observed variables were amount of spikelet per spike, amount grain of spikelet, amount of floret per spike, spikelet length and width, grain length and width, amount of full grain, amount of unfull grain and a thousand grain weight. The result showed that UAGDM 13 had a good amount of spikelet per spike. All genotypes had high amount of floret per spike except UAGDM16. A good spikelet length was belonged to all genotypes except UAGDM11 and UAGDM13. Grain length and width were not significant among all genotypes. Three genotypes which had a high amount of full grain were UAGDM5, UAGDM6 and UAGDM17. Genotype UAGDM1 was the best of a thousand grain weight.